Le Développement Vocationnel de l’Adulte et la Notion d’Acteur - Riverin-Simard, Danielle; Spain, Armelle; Michaud, Clémence (Canadian Journal of Counselling and Psychotherapy, 2007)
The notion of actor is used increasingly in the field of career counselling. In an attempt to better understand this concept and to see how it could be transferred to the field of career development, this article provides a brief overview of how this notion has evolved within the field of sociology, and particularly within the current of sociology emphasizing action. In this context, the article explains how the notion of actor fits into the authors' work, in particular concerning the career development of adults struggling with professional discontinuity. Finally, the authors suggest ways to use this concept in order to shed new light on research and practice in career counselling